2017
DOI: 10.1016/j.jobcr.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of pH and calcium ions release from different calcium hydroxide pastes at different intervals of time: Atomic spectrophotometric analysis

Abstract: Intra canal medicamentAtomic absorption spectrophotometer pH a b s t r a c t Aim: To evaluate the effect of different vehicles on pH and release of calcium ions from calcium hydroxide (CH) paste from apical third of root canals.Methods: 40 single rooted extracted human mandibular premolars were instrumented with RevoS files (MicroMega) up to ISO size 40. The teeth were divided into 4 groups on the basis of vehicle as follows: Group I -calcium hydroxide mixed with 2% chlorhexidine; Group II -calcium hydroxide m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Further, a WMTA modified by Saghiri et al had nanoscale-sized particles that increased the calcium ion release significantly, affecting hard tissue regeneration to a high degree [10]. Calcium ions also influence tissue mineralization by fastening cell proliferation when present in large quantities [15]. The modified MTA in the present study demonstrated improved hard tissue regeneration potential (as shown in the results of the EDS tests), confirming that calcium ion release is higher in modified MTAs.…”
Section: Discussionsupporting
confidence: 81%
“…Further, a WMTA modified by Saghiri et al had nanoscale-sized particles that increased the calcium ion release significantly, affecting hard tissue regeneration to a high degree [10]. Calcium ions also influence tissue mineralization by fastening cell proliferation when present in large quantities [15]. The modified MTA in the present study demonstrated improved hard tissue regeneration potential (as shown in the results of the EDS tests), confirming that calcium ion release is higher in modified MTAs.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, using intracanal medicament is necessary to protect the root canal system during root canal treatment. 35,36 Several additives have been combined with MTA to enhance the working properties of the cement. It has been demonstrated that NaOCl gel may reduce the setting time and improve the handling characteristics of the mixture.…”
Section: Discussionmentioning
confidence: 99%
“…44 In this study, the release of calcium ions was assessed to check that CHX gel use does not interfere with the dissociation of calcium ions from experimental medicaments and also that it does not decrease pH values. Misra et al 35 studied the release of calcium ions and the pH of calcium hydroxide paste when mixed with different vehicles, and found that the calcium hydroxide with glycerine showed a highest calcium ion release followed by calcium hydroxide with chlorhexidine. The methodology used in this study to analyze the calcium ion release was similar to work done in the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Misra also observed an increase of Ca 2+ rate of Ca(OH) 2 in double distilled water from day 1 to day 2 and day 7, however it then declined in day 15 and 30 period of observation, they concluded that the use of aqueous vehicle for Ca(OH) 2 resulted in a rapid initial ionic dissociation which will decreased consequently. 17 Several factors can affect the release of Ca 2+ namely, solvent, viscosity, particle size, the ratio of powder to liquid and contamination. 13,16,18 Viscosity of a material affects the release of Ca 2+ , a low viscosity vehicle will dissociate the Ca 2+ and OHions faster because they will have less inner particle interaction, but not as stable as a viscous solvent.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Since the release of inorganic ions namely, Ca 2+ plays an important task in the effectiveness of dental materials, many studies have been carried out to measure the Ca 2+ ions released by different kinds of dental material. [15][16][17][18] Considering the newly developed material has not comprehensively evaluated particularly in its bioactivity by releasing Ca 2+ ions, our study aimed to evaluate the Ca 2+ release rate of the Ca(OH) 2 prototype from Indonesian limestone at different interval of time using an atomic spectrophotometer.…”
Section: Ca(oh)mentioning
confidence: 99%